Tei-Index in patients with mild-to-moderate congestive heart failure - Bruch, C; Schmermund, A; Marin, D; Katz, M; Bartel, T; Schaar, J; Erbel, R (European heart journal, 2000)
Background Congestive heart failure is related to contraction and relaxation abnormalities of the ventricle. Isolated analysis of either mechanism may not be reflective of overall cardiac dysfunction. A combined myocardial performance index (isovolumic contraction time plus isovolumic relaxation time divided by ejection time, ‘Tei-Index’) has been described which may be more effective for analysis of global cardiac dysfunction than systolic and diastolic measures alone. It was the aim of the present investigation to evaluate the Tei-Index against invasive examination. Methods and Results Eighty-one subjects were included in a consecutive manner, among 125 patients undergoing left heart catheterization for invasive measurement of left ventricular end-diastolic pressure; 43 patients had congestive heart failure (35 male, 8 female, 68±6 years) defined by NYHA functional class ≥2 (mean 2·5±0·5) and left ventricular end-diastolic pressure ≥16mmHg (mean 20±4) and 38 subjects (32 male, 6 female, 66±5 years) without symptoms of heart failure (NYHA functional class I) and with normal left ventricular end-diastolic pressure (mean 12±3mmHg) served as a control group. Using conventional echo-Doppler methods, parameters assessed were: ejection fraction, peak velocities of early (E) and late (A) diastolic filling, the E/A ratio, deceleration time, isovolumic contraction time, isovolumic relaxation time and ejection time. The Tei-Index was obtained by subtracting ejection time from the interval between cessation and onset of the mitral flow. The control group and patients with congestive heart failure did not differ with respect to the E/A ratio (0·86±0·27 vs 0·90±0·44, P=ns), deceleration time (203±42ms vs 206±36ms,P =ns) and isovolumic relaxation time (97±16ms vs 94±26ms, P=ns). The ejection fraction was slightly reduced in patients with congestive heart failure (46±11% vs 55±8%,P <0·05). The Tei-Index was easily and reproducibly measured in all subjects. The mean value of the Tei-Index was significantly different between the control group and patients with congestive heart failure (0·39±0·10 vs 0·60±0·18, P<0·001). Receiver operating characteristic curve analysis for the Tei-Index yielded an area under the curve of 0·88±0·038. Using a Tei-Index ≥0·47 as the cutpoint, congestive heart failure was identified with a sensitivity of 86% and a specificity of 82%. No correlation was observed between the Tei-Index and heart rate (r=0·22, P=ns), systolic blood pressure (r=0·16,P =ns) or diastolic blood pressure (r=0·08, P=ns). The Tei-Index was significantly related to left ventricular end-diastolic pressure (r=0·46,P <0·01). Conclusion The Tei-Index is a sensitive indicator of overall cardiac dysfunction in patients with mild-to-moderate congestive heart failure. The Tei-Index is easily obtained and may be used in the work-up of patients with suspected cardiac dysfunction.